Verbos do inglês acadêmico escrito e suas colocações: um estudo baseado em um corpus de aprendizes brasileiros de inglês - Annallena de Souza Guedes (2017)
Studies with learner corpora (HUNSTON, 2002) have contributed to the research in the foreign language teaching and learning area, mainly when linguistic analysis approaches, such as the Contrastive Interlanguage Analysis (CIA) (GRANGER, 1996), are used. CIA aims at comparing learners production to native speakers corpora, embedded in academic contexts. Considering the principles of the Contrastive Interlanguage Analysis (CIA), this research has the goal to analyze the writing of Brazilian university students in argumentative essays, verifying the use and the patterns of use of Verbs from the Written Academic ENGLISH (VWAE), understood here as more typical verbs of the academic context (GRANGER & PAQUOT, 2009). Due to this central objective, this study also aims at analyzing the most frequent collocations (verb + -ly adverbs) due to the importance of these phraseological units for the linguistic pattern comprehension. We have assumed that there is a tendency to speakers whose first language (L1) is not English to make certain lexical choices (GILQUIN; PAQUOT, 2007) that differ from the native speakers patterns of use. In the light of the context the corpora analyzed were compiled, this study is originated from the wish of analyzing the frequency, use and patterns of use of Verbs from the Written Academic English, used by university students. For such, we analysed the argumentative essays in CorIFA (Corpus of English for Academic Purposes), compiled at the Federal University of Minas Gerais and we compared it to the argumentative essays of BAWE (British Academic Written English), compiled in the United Kingdom. Hence, we use Corpus Linguistics tools, since they allow us to see the use of grammatical categories. The results of this research showed that there is a great lexical variation of verbs and -ly adverbs in both subcorpora; however, in CorIFA subcorpus, there is less lexical variation in relation to VWAEs, which demonstrates learners preference to use the same verbs, maybe, due to a proficiency issue. The results pointed out to the preference of using the verbs, semantically classified as action verbs (e.g apply and provide). In relation to collocations, it was not possible to identify the associate strength between verbs and -ly adverbs in both subcorpora because of their low frequency. We conclude that the analysis of CorIFA subcorpus shows that the Brazilian university learners trust the use of lexis that is more familiar to then, in the case of the studied VWAEs, as well as in the combinations verb + -ly adverb. This study may be the basis for future pedagogical interventions focused on learners' needs in the same level as the CorIFA subcorpus participants.